ANALYSIS OF NUTRITIONAL COMPOSITION IN ONION STICKS WITH THE ADDITION OF PATIN FISH (PANGASIUS HYPOPHTHALMUS) MEAT FLOUR - Junianto Junianto; Rani Pratiwi (Universitas Mataram, 2024)
Increasing catfish production must be accompanied by increasing its utilization. One form of utilization of catfish is to make fish meal because it has wide applications in the food sector. Catfish meat meal can be applied as an additional ingredient in the formulation for making onion sticks. The application of adding catfish meat flour to onion stick products has an impact on the level of liking. The addition of 15% catfish meat flour to the formulation for making onion sticks produces the most preferred product. This research aims to analyze the proximate composition of onion sticks with the addition of 15% catfish meat flour. This experimental method is a non-designed experiment with two treatments with levels of addition of catfish meat meal. Treatment A added 0% catfish meat meal as a control and treatment B added 15% catfish meat meal. The parameters observed were the proximate composition of onion sticks including water content, ash content, fat content, protein content and carbohydrate content. The data obtained was analyzed comparatively descriptively. Based on the research results, it was found that the proximate analysis contained in the treatment of 15% addition of catfish meat flour to onion sticks was a water content of 4.35%; ash content 2.17%; fat content 36.56%; protein content 9.31% and carbohydrate content 47,61%.